The Effectiveness of a Learning Program Based on Critical Thinking Skills in the Achievement of Human Geography among Sixth-Grade Literary Students - Hadi, Malik Ghazi (Journal of Innovation in Education and Social Research, 2026)
This research aims to identify the effectiveness of a learning program focused on critical thinking skills in achieving human geography among sixth-grade literary students. A quasi-experimental design was used in this study. The research sample was a random selection consisting of 60 sixth-grade literary students, who were divided into two groups: An experimental group studied according to an educational program that included methods based on critical thinking skills (such as systems thinking, complex problem-solving skills, and the ability to predict), while another control group studied traditionally. Results show statistically significant differences in favor of the experimental group, which could be attributed to critical thinking skills as a contributor to geographical understanding and academic achievement at their highest levels. Well into the twenty-first century, educational systems are undergoing radical changes that aim to break away from traditional models of knowledge transfer and adopt a range of strategies to enhance learners' cognitive efficiency. This has coalesced around the idea that learning is no longer about rote memorization of geographical data or population numbers, but rather about how to handle those datasets when encountered, to understand spatial variability, and to quantitatively analyze the intrinsic relationships between humans and their environment. Critical thinking skills are a modern area of education. Still, they will prepare students to think consciously and systematically, as reflected in their best academic results and decision-making abilities. Thought out decisions on geopolitics at present. This study aims to evaluate the theoretical and procedural aspects, as well as the actual results, of this application, which constitutes a learning program based on these skills for sixth-grade literary students in Babylon Governorate.